The Impact Of Fiscal Policy On Economic Growth - Omar Al-Kasasbeh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The relationship between fiscal policy and economic growth has attracted a great deal of attention in recent years. The growth experience of several countries during the last decades has generated a growing strand of theoretical and empirical literature trying to explain these events. Although one could argue that economic growth and fiscal policy influence each other. The aim of this paper is to review the research work conducted on fiscal policies and economic growth, noting that there are three tools of fiscal policy; the first type is government expenditure, the second type is taxation, and the third type is debts. In addition, according to previous research, the relationship between fiscal policy and economic growth is not clear and consistent, where in some cases a positive relationship, while in others it may be a negative relationship. In this paper, we will discuss the concept of fiscal policies, economic growth, and the relationship between those two variables through some of the previous research.